2009
DOI: 10.1152/ajpregu.00199.2009
|View full text |Cite
|
Sign up to set email alerts
|

Novel bUT-B2 urea transporter isoform is constitutively activated

Abstract: Our previous studies have detailed a novel facilitative UT-B urea transporter isoform, bUT-B2. Despite the existence of mouse and human orthologs, the functional characteristics of UT-B2 remain undefined. In this report, we produced a stable MDCK cell line that expressed bUT-B2 protein and investigated the transepithelial urea flux across cultured cell monolayers. We observed a large basal urea flux that was significantly reduced by known inhibitors of facilitative urea transporters; 1,3 dimethylurea (P < 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
4
15
0
Order By: Relevance
“…This result is similar to a previous study for the MCT1 short-chain fatty acid transporter, whose abundance did not differ between dorsal and ventral sacs in developing calves (Flaga et al 2015). Since we have previously reported that UT-B2 transporters are constitutively activated (Tickle et al 2009), this strongly suggests that overall there will be no difference in UT-B mediated trans-epithelial transport in different ruminal sacs at the cellular level. However, in contrast to this, physical measurements showed that there were significant differences in the size of papillae from the three ruminal sacs, with those from the dorsal sac being considerably smaller (Table 1).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result is similar to a previous study for the MCT1 short-chain fatty acid transporter, whose abundance did not differ between dorsal and ventral sacs in developing calves (Flaga et al 2015). Since we have previously reported that UT-B2 transporters are constitutively activated (Tickle et al 2009), this strongly suggests that overall there will be no difference in UT-B mediated trans-epithelial transport in different ruminal sacs at the cellular level. However, in contrast to this, physical measurements showed that there were significant differences in the size of papillae from the three ruminal sacs, with those from the dorsal sac being considerably smaller (Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…d In contrast, preincubation of hUTBc19 with the same concentration of a nonspecific peptide (1 lg/ml) had minimal effect on the strong stratum basale staining. Scale bar represents 100 lm protein was deglycosylated to a core protein of *40 kDa, which is similar to the *36 kDa protein previously reported for bovine UT-B2 using a different antibody (Simmons et al 2009;Tickle et al 2009). The weak, unglycosylated signals obtained in the cytoplasm-enriched protein sample are most likely non-specific signals, similar to those previously observed with the hUTBc19 antibody (Walpole et al 2014).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…UT-A1 and UT-A3 are cAMP-regulated urea transporters expressed in kidney tubule epithelia. [23][24][25] MDCK cells were cultured on collagen-coated porous filters for measurement of urea accumulation in the apical solution (basolateral to apical transport) after addition of urea to the basolateral solution. The top panel in Figure 5A show increased urea permeability in each of the transfected cell lines.…”
Section: Ut-b Inhibition Mechanism and Specificitymentioning
confidence: 99%
“…In other mammals, particularly ruminants, there is gathering evidence that these transporters allow the passage of blood urea into the lumen of the gastrointestinal tract (20,22,31,33). They therefore play a vital role in the urea nitrogen salvaging (UNS) process in which urea supplied by the host is broken down by bacterial urease to release nitrogen for bacterial growth.…”
mentioning
confidence: 99%